2008
DOI: 10.1177/039463200802100334
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Long-Lasting Persistent Allergic Rhinitis in Adolescents

Abstract: While it is well known that asthma is characterized by airway remodelling, only few studies have investigated this issue in patients affected by allergic rhinitis (AR). The aim of the present study is to investigate functional and structural consequences of long-lasting persistent AR (PER) in a cohort of adolescents. Eighty patients, forty with short-lasting and forty with long-lasting PER were prospectively and consecutively evaluated both clinically and by performing skin prick test, nasal cytology, and rhin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Increased levels of TSLP in nasal mucosa of patients affected by allergic rhinitis have been reported by Mou (17)(18) and, in a recent study, Liu et al showed high levels ofTSLP in nasal epithelial layer of patients with nasal polyps (19).…”
mentioning
confidence: 78%
“…Increased levels of TSLP in nasal mucosa of patients affected by allergic rhinitis have been reported by Mou (17)(18) and, in a recent study, Liu et al showed high levels ofTSLP in nasal epithelial layer of patients with nasal polyps (19).…”
mentioning
confidence: 78%
“…Indeed, continuous exposure to mite allergen induces the persistence of inflammatory phenomena, which induce worsening of respiratory function [17]. In this regard, it has been reported recently that the duration of mite allergy induces a significant reduction of nasal airflow in adolescents [18]. Chronic nasal inflammation is also likely to result in hypertrophy of the nasal turbinates, thus inducing impaired passage to airflow.…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 was cloned as a gene induced by IL-18, and the fact that IL-32related cytokines, TNFa. and IL-18 show a close correlation with inflammatory diseases implies that IL-32 has a pathologic role in inflammation (22)(23)(24)(25)(26).…”
mentioning
confidence: 97%